Emergent Processes - Tom Wiscombe (Oz, 2005)
This century is going to be about biology. I don’t want to confuse architecture with biology. You can take analogies too far of course. But, as Gödel once said in his Theory of Incompleteness, sometimes to solve a problem in a particular discipline, you have to switch to completely different territory.